Simulation and Analysis on Performance of Space-Time Coding in MIMO - Shequan Jiang; Jing Wang; Chao Peng (Dianxin kexue)
The theory of layered space-time code,space-time block code,space-time trellis code were introduced, and the technology of combing STC and OFDM was researched.Then,several MIMO system models were built in different STC conditions and their BER performances were simulated. The simulation results were analyzed. Finally, the advantages and disadvantages of three kinds of STC and the advantages of STC-OFDM were summarized. Some other application combined with STC such as cooperative relay transmission system and the prospect of STC were discussed.